The Influence Of Financial Compensation And Work Ethic On The Organizational Commitment Of Employees At PT Perkebunan Nusantara IV Work Unit Palm Oil Mill (PKS) Gunung Meliau - Agustina Icha Mawarni; Devi Yasmin (UNIVED Press, 2024)
The purpose of this study is to examine the impact of financial compensation and work ethic on the organizational commitment of employees at PTPN IV Gunung Meliau Palm Oil Mill Unit. This research employs a quantitative approach. The sample in this study consists of all employees of PTPN IV Gunung Meliau Palm Oil Mill Unit, totaling 125 employees. This study uses multiple linear regression, correlation coefficient, coefficient of determination, F-test, and t-test. The results indicate that financial compensation and work ethic simultaneously affect organizational commitment. Furthermore, financial compensation and work ethic partially have a significant impact on organizational commitment